Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan pada Perusahaan Ritel Indeks LQ45 Periode 2019-2023 - Lis Lestari Sukartiningsih; Selda Qoennezzia Gabriella (Akubis : Jurnal Akuntansi dan Bisnis, 2024)
This study aims to analyze financial ratios to assess financial performance in LQ45 retail companies index for the 2019-2023 period. The type of research is a case study. The data collection method is a literature study and documentation data collection techniques are secondary data in financial reports. The population used was 32 retail companies listed on the IDX for the 2019-2023 period. After using the purposive sampling method, 3 companies were selected. The results of the financial ratio analysis of PT Ace Hardware Tbk have good financial performance values. This is seen from the DAR, DER, LTDR, FATR, NPM, ROA, BV, and M/B Ratio ratios which are at the appropriate industry standards. PT Erajaya Swasembada Tbk has good financial performance as seen from the LTDR, ITR, FATR, DPR, and BV ratio values ​​which are at the appropriate industry standards. PT Sumber Alfaria Trijaya Tbk also has good financial performance. This is seen from the LTDR, ITR, FATR, ROA, DPR, BV, M/B Ratio ratio values ​​which are at the appropriate industry standards.